Consequences on Network Security and Cryptography - Inbavalli, M; Ammulu, T (International Journal of Computer Sciences and Engineering, 2025)
Network securities have become a gambol in our whole world. The need of network security is accelerate at the same speed of better internet usage. The first and prime thing of every network design, plan, build and operating a network is the importance of a strong security. Information security is the great basic issue in an assurance safe transmission of data. Network security and cryptography is a concept to protect network and data transmission over wireless network. More users connect to the internet is attracts a lot of cyber attacks. Data securities are the main feature of safe data transmission above changeable network. User chooses is assign an id and password and figure print or network authentication information that allows them access to information and program within their authority. The internet structure itself allowed for more security threats to occur.